PJOK Teachers' Perceptions of The Independent Curriculum in The Primary School of Wahidin Sudirohusodo Kec. Batang - Pamungkas, Depo Dana; Wijaya, M. Riski Adi; Panggraita, Gilang Nuari; Yusuf, Jamaludin (Jurnal Pendidikan Jasmani (JPJ), 2024)
This research aims to describe the perceptions of PJOK teachers towards the independent curriculum in elementary schools in the Wahidin Sudirohusodo Cluster, Batang District. This type of research is descriptive qualitative. The subject of this research was the PJOK teacher of the Wahidin Sudirohusodo group, Batang District. Data collection techniques are carried out through interviews, observation and documentation. The data analysis technique was carried out descriptively qualitatively by collecting data, reducing data, presenting data and withdrawing data. The results of the research show that PJOK Teachers' Perceptions of the Merdeka Curriculum in SE-Gugugus Wahidin Sudirohusodo Elementary School, Batang District, namely a curriculum whose learning is freed up or modified according to the needs of students, which has 2 distinctive characteristics, namely Differentiated Learning and the Project for Strengthening the Pancasila Student Profile or P5, aims to to develop students' potential and interest in learning, students have the freedom to think and express themselves, teachers teach according to the students' stage of achievement and development. The socialization of the independent curriculum in the form of bintek was felt to be less effective because the delivery time was too short and the material was very complex. There are 4 things in independent curriculum learning planning, namely the first is understanding learning outcomes, the second is formulating learning objectives, the third is arranging the flow of learning objectives, the fourth is designing learning. After these four things are done, the teacher creates a learning module. The implementation of independent curriculum learning focuses on essential material, developing student competencies in each phase. using a differentiation approach, and implementing P5. Evaluation of independent curriculum learning is by carrying out 3 evaluations, namely diagnostic, formative and summative. The way teachers adapt the two curricula in schools is to plan, implement and evaluate 2 curricula. The difficulties faced by the PJOK SE-Gugugus teacher Wahidin Sudirohusodo in implementing the independent curriculum in the Batang District Elementary School, namely the absence of PJOK independent curriculum package books as a learning resource for children, limited classroom space, lack of laboratory or library facilities, teachers still have experience with independence. low learning, limited references, uneven access to learning, time management, teachers lacking mastery of the material presented, programs that have not been achieved and inadequate facilities.